Evaluation of cross-protection of a reduced-dose PRRS MLV vaccine against the NADC30-like PRRSV challenge - Liu, Jiayu; Yan, Xinyu; Wu, Wensi; Li, Yan; Xing, Shuaibin; Zhao, Shan; Huang, Xiaobo; Zhao, Qin; Wen, Yiping; Cao, Sanjie; Du, Senyan; Yan, Qigui; et al. (Frontiers in Veterinary Science, 2024)
IntroductionAt present, the NADC30-like strain has become the prevalent strain of PRRSV in China. Many studies have found that existing commercial vaccines are ineffective or provide only limited protection. No study has investigated the cross-protection of different dosages of commercial MLV vaccines against NADC30-like PRRSV. Therefore, this study assessed the effectiveness of various dosages against a NADC30-like PRRSV infection using commercial PRRSV vaccines, Ingelvac PRRS MLV, which have been widely utilized in China.MethodsIn this study, we immunized piglets with four different dosages of the MLV vaccine and infected piglets within a nasal way with NADC30-like CF PRRSV at 28 days post-vaccination. We observed the status of pigs before and after the challenge of NADC30-like PRRSV CF strain and reflected the protective effect of different dosages of MLV vaccine through multiple assays.ResultsCompared to those piglets immunized with 1 dosage, the piglets immunized with 0.01 dosage had better performance, such as the highest average daily gain before the challenge, lesser lesions and viremia after the challenge, low clinical score, and stable temperature during the study. However, the piglets immunized with 0.01 dosage still showed viremia, viruses were detected in their lungs, tonsils, and inguinal lymph nodes, and pathological lesions occurred in their lung. Immunohistochemistry staining of the lung of vaccinated piglets revealed a similar viral load to that of unvaccinated piglets, suggesting that immunization could not completely remove the virus from the vaccinated piglets’ tissues.DiscussionOur research suggests that the MLV vaccine could provide limited protection against the NADC30-like PRRSV infection, and lowering the dosage to 0.01 may produce better protective efficacy. In the context of identifying the immunological target, comprehending the virulence of the virus in the field, and guaranteeing safety, we might be able to reevaluate vaccination dosages to achieve higher economic value.